Portuguese cork industry: filling the knowledge gap regarding occupational exposure to fungi and related health effects - Viegas, Carla; Dias, Marta; Pacífico, Cátia; Faria, Tiago; Clérigo, Anália; Brites, Hermínia; Caetano, Liliana Aranha; Carolino, Elisabete; Gomes, Anita Quintal; Viegas, Susana (Frontiers in Public Health, 2024)
Introduction The presence of the Penicillium section Aspergilloides (formerly known as Penicillium glabrum) in the cork industry involves the risk of respiratory diseases such as suberosis. Methods The aim of this study was to corroborate the predominant fungi present in this occupational environment by performing a mycological analysis of 360 workers’ nasal exudates collected by nasal swabs. Additionally, evaluation of respiratory disorders among the cork workers was also performed by spirometry. Results Penicillium section Aspergilloides was detected by qPCR in 37 out of the 360 nasal swabs collected from workers’ samples. From those, 25 remained negative for Penicillium sp. when using culture-based methods. A significant association was found between ventilatory defects and years of work in the cork industry, with those people working for 10 or more years in this industry having an approximately two-fold increased risk of having ventilatory defects compared to those working less time in this setting. Among the workers who detected the presence of Penicillium section Aspergilloides, those with symptoms presented slightly higher average values of CFU. Discussion Overall, the results obtained in this study show that working in the cork industry may have adverse effects on worker’s respiratory health. Nevertheless, more studies are needed (e.g., using serological assays) to clarify the impact of each risk factor (fungi and dust) on disease etiology.